ARSITEKTUR UNTUK RAKYAT? SUATU KAJIAN TENTANG PENDEKATAN PERANCANGAN PARTISIPATIF - Djaja Bharuna, Anak Agung Gde (Jurnal Natah; Vol. 2, No. 1 Februari 2004)
The general topic in this paper is architecture for people on low pyment who live in rural urban area ( city ), in Indonesia. The main frame in this paper is the solution that directed to discussion about Participatory Design Approach ( PDA ). The proportion of discussion on this paper direction for most home problem, because in fact is nearest architect figure by the people. This paper has two big substansial issues. The first issue is culture issue that studying participation design and the potency in architecture area as a culture product, and the second issue is a political issues that studying by approach national building area that containing ideology problem as solution this problem. Both of those issue never truly partial, they let it mixed and colored this paper dynamically. The final dicuss of political issue placed on conclusion, and cultural issue will be theoretical discuss that bring up the regional potency ( regionalism ) of traditional architect.
Keywords: house, kampung – kota, participatory design approach.